EFFECT OF PROTEIN CONCENTRATE WITHDRAWAL AND REDUCING THE CRUDE PROTEIN IN DIETS AND ADDING AMINO ACIDS ON PRODUCTION PERFORMANCE OF LAYING HENS - Al-Bayati, Omar I.; Al-Mashhadani, Hisham A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The study was aimed to demonstrate the effect of withdrawing the protein concentrate and reducing the crude protein to the level of (16 and 15%) in the diets and supplementing them with a mixture of amino acids (methionine, lysine and threonine) at a rate of 1, 1.5, 2% on the productive performance of laying hens. 128 laying hens of the Lohmann Brown were used, at the age of 21 weeks. They were randomly distributed in to 8 treatments, with 8 replications for each treatment, as each replicate includes 2 chickens (16 chickens/treatment). The experimental treatments were as follows: T1 the control (standard diet), T2 a treatment devoid of the protein concentrate, and the T3, T4, and T5 Reducing the percentage of crude protein by 1% and adding a mixture of amino acids by 1, 1.5, and 2%, respectively , and the T6, T7, and T8 Reducing the percentage of crude protein by 2% and adding a mixture of amino acids by 1, 1.5, and 2%, respectively. The results showed that there were no significant differences in the interaction rates for the protein reduction treatments 1 and 2%, but it was observed that there was a significant superiority (P>0.05) in egg production, egg weight rate, feed consumption rate, feed conversion efficiency, egg mass and rate of body weight is in favor of treatments adding a mixture of amino acids at a rate of 1.5 and 2% and with a reduced percentage of protein 1 and 2% compared to the control treatment with out of the protein concentrate. It can be concluded from this study that adding a mixture of amino acids at a rate of 1.5 and 2% and reducing the percentage of protein by (1 and 2%) led to a significant improvement in most productive traits compared to the control treatment (with out of protein concentrate).